Automatised extraction of optical and THz properties from experimental multilayer transmission data - Siti Nur Amalini Mansor (Nanyang Technological University, 2022)
Terahertz time-domain spectroscopy is used to extract the complex dielectric properties of materials. Sometimes, researchers need to carry out simulations which require the material properties of their sample. There exist available sources for properties of common materials but often these do not perfectly describe the researcher’s sample. This thesis focuses on making adjustments to the referenced material properties such that the simulation turns out accurate. In developing software for this task, we (1) derive a transfer matrix method that can simulate the propagation of a THz signal through a material, given its properties, and (2) formulate an optimization problem to find the properties that fit the simulated transmitted signal to an experimentally measured one. This software is flexible in the sense that it can find either the (1) relative permittivity, (2) refractive index and extinction coefficient, or (3) plasma frequency and damping constant of the material. We used four optimization methods to test the software and found that only one – Powell – was consistent.